Fate and Prediction of Phenolic Secoiridoid Compounds throughout the Different Stages of the Virgin Olive Oil Making Process - Giuseppe Fregapane; M. Desamparados Salvador (MDPI AG, 2017)
The evolution of the main phenolic secoiridoid compounds throughout the different stages of the virgin olive oil making process-crushing, malaxation and liquid-solid separation-is studied here, with the goal of making possible the prediction of the partition and transformation that take place in the different steps of the process. The concentration of hydroxytyrosol secoiridoids produced under the different crushing conditions studied are reasonably proportional to the intensity of the milling stage, and strongly depend on the olive variety processed. During malaxation, the content of the main phenolic secoiridoids is reduced, especially in the case of the hydroxytyrosol derivatives, in which a variety-dependent behaviour is observed. The prediction of the concentration of phenolic secoiridoids finally transferred from the kneaded paste to the virgin olive oil is also feasible, and depends on the phenolic content and amount of water in the olive paste. The determination of the phenolic compounds in the olive fruit, olive paste and olive oil has been carried out by LC-MS (Liquid-Chromatography Mass-Spectrometry). This improved knowledge could help in the use of more adequate processing conditions for the production of virgin olive oil with desired properties; for example, higher or lower phenolic content, as the amount of these minor components is directly related to its sensory, antioxidant and healthy properties.